Evaluation of the Antibacterial and Anti-Inflammatory Effects of a Natural Products-Containing Toothpaste - Qi, Cai; Peng, Xian; Yuan, Shaotang; Zhang, Miaomiao; Xu, Xin; Cheng, Xingqun (Frontiers in Cellular and Infection Microbiology, 2022)
Fluoride-containing toothpaste is daily used in toothbrush. Some compounds derived from natural herbs that have antibacterial and anti-inflammatory activities has attracted increasing attention as potential supplements for the control of oral diseases. In this paper, a natural product mixture (NPM-8) containing eight herbs extracts was added to toothpaste, and its antibacterial and anti-inflammatory effects were investigated. The results showed that NPM-8-containing toothpaste exhibited superior and faster inhibitory and bactericidal effects against S. mutans, S. sanguinis and P. gingivalis than that of the NPM-8-free toothpaste. NPM-8-containing toothpaste significantly reduced the biomass of single-species or three-species biofilms. The cytotoxicity of the NPM-8-containing toothpaste was similar to that of the conventional fluoride toothpaste and CHX. The NPM-8-containing toothpaste could significantly inhibit IL-1β and IL-6 production in HGE cells and exhibited a better anti-inflammatory effect than that of the NPM-8-free toothpaste. In conclusion, NPM-8-containing fluoride toothpaste is superior to conventional fluoride toothpaste in regard to their antibacterial, antibiofilm, and anti-inflammatory properties. NPM-8-containing toothpaste also has good biocompatibility and is safe for daily use. It indicates that NPM-8 is a promising natural product mixture in oral health.